Luminescence of bound excitons created near sodium impurity ions in KCl:Na single crystals - K. Shunkeyev; А. Kenzhebayeva; A. Krasnikov; V. Nagirnyi; Sh Sagimbayeva; D. Sergeyev; А. Tilep; Zh Ubaev; A. Lushchik (Optical Materials: X)
The study is focused on luminescence features of bound excitons (exciton-like formations, ELFs) in KCl:Na single crystals created in the field of sodium impurity ions either directly at photoexcitation or via the recombination of electron-hole pairs. The intensity of the X-ray luminescence (XRL) bands peaked at 2.8 and 3.1 eV (emission of recombinationally formed and relaxed ELFs) increases with both, the concentration of sodium impurity ions (10 → 1000 ppm) and the detection temperature (85 → 350 K). It is worth noting that at room temperature, the light yield of these XRL bands in KCl:Na practically coincides with that for the luminescence measured in the same way in classical scintillators, CsI and CsI:Na crystals. The lifetime of the fast component of cathodoluminescence at 2.8 and 3.1 eV equals 2.4 and 1.7 ns, respectively, at 6 K and even shortens to approximately τ ≈ 0.3 ns at room temperature. At 10 K, photons of 7.6 and 6.7 eV directly form ELFs in the field of single or paired Na+ impurity ions with typical luminescence bands peaked, respectively, at 2.8 eV (el0 (Na+)) and 3.1 eV (el0 (Na+-Na+)). These photoluminescence bands undergo complete thermal quenching by 200–300 K, whereas relevant XRL bands are not quenched up to 350 K, their intensity even noticeably increases at 200 → 350 K.